Longitudinal relationship of diabetes‐related distress and depressive symptoms: analysing incidence and persistence. Issue 10 (20th August 2015) - Ehrmann, D.; Kulzer, B.; Haak, T.; Hermanns, N.
Abstract Aim To investigate the longitudinal bi‐directionality of diabetes‐related distress and depressive symptoms. Methods A total of 509 patients receiving intensified insulin therapy completed the Centre for Epidemiological Studies Depression scale questionnaire for the assessment of depressive symptoms as well as the Problem Areas in Diabetes questionnaire for the assessment of diabetes‐related distress at baseline and at 6‐month follow‐up. Separate logistic and linear regression analyses for incidence and persistence were performed with demographic (age, gender, BMI) and medical (diabetes type, HbA1c, diabetes duration, late complications) control variables. Results Diabetes‐related distress at baseline increased the risk of the incidence of elevated depressive symptoms by 2.56‐fold (odds ratio 2.56; 95% CI 1.15–5.72; P = 0.02) when controlling for demographic and medical variables. In addition, diabetes‐related distress at baseline doubled the chance of the persistence of elevated depressive symptoms (odds ratio 2.04, 95% CI 1.04–3.99; P = 0.04) when controlling for demographic and medical variables. The chance of having persistent elevated diabetes‐related distress was increased 5.94‐fold (odds ratio 5.94, 95% CI 2.60–13.59; P < 0.0001) when elevated depressive symptoms were present at baseline. None of the medical variables had an influence on incidence or persistence. Conclusions Diabetes‐related distress was identified as a risk factor for the incidence and persistence of depressive symptoms. Reducing diabetes‐related distress could help to prevent the development of elevated depressive symptoms. Furthermore, depressive symptoms were identified as an amplifier for diabetes‐related distress. Diabetes‐related distress and depressive symptoms were independent risk factors for each other and should be monitored in routine care to disentangle their influence.